Evaluation of antihypertensive drug use in preeclampsia and eclampsia patients in the inpatient room of Bandung Regency Hospital - Sutrisno, Entris; Selifiana , Nita; Sodik , Jajang Japar; Agustin, Ia Nurfauziah (Institute of Computer Science (IOCS), 2024)
Indonesia is one of the third highest developing countries in ASEAN with maternal mortality rate (MMR) and infant mortality rate (IMR). One of the three main causes of pregnancy-related maternal deaths is hypertension during pregnancy. It is very important to get rational antihypertensive therapy immediately in order to maintain normal blood pressure. This study aims to determine the profile of the use and rational use of antihypertensive drugs in preeclampsia and eclampsia patients in the Inpatient Room of Bandung Regency Hospital. The study was conducted observational with retrospective data collection. Samples were taken by random sampling which met the inclusion criteria for the period January-December 2021. The rationality of antihypertensive drug use is based on the 2019 American College of Obstetrics and Gynecologists and PIONAS guidelines. There were 78 medical records that met the criteria. The characteristics of the majority of patients aged 21-35 years (64%) with a gestational age of 28-40 weeks (97%) and the antihypertensive drug therapy that was widely used was nifedipine (56%). The percentage of rational use of antihypertensive drugs showed the right indication (100%), the right drug (95%), the right dose (100%), and the right frequency (100%).